Michael Casimir Radziwiłł‘S Named Rybeńko (1702–1762) Diary: Between Itinerarium and Egodocument - Veličkaitė, Vika (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]The article to try to analyze specifics of Kazimierz Michał Radziwiłł called Rybeńko diary in the context of egodocuments research. The diary was written almost all conscious noble‘s life and reveals specifics of Baroque culture as well as individual features. The first chapter presents the specifics of the diary which is very useful for itinerary research, but the content and volume of diary also lets us to research noble‘s character, his relationships with family, his health issues etc. Also this diary is useful for interdisciplinary research to reconstruct ways of treatments, alcohol effect on Radziwiłł’s personality etc. Diary was practical auxiliary tool for reconstruction of important facts in Radziwiłł’s life, also it had medical history function. The second chapter presents the M. K.Radziwiłł personality features, relationship with family members. Auto ironicaland anxious nobleman fostered warm relations with his first wife, Frances Urszula Wysniowiecka Radziwiłłowa and his daughter Teofilia. Relations with the domineering mother Hanna Sanguszka Radziwiłłowa was much tenser. Also emerging Baroque influence the personality worldview and approachto death in the diary. Radziwiłł opens us as obstinate, self-willed, emotive, venturesome person, but very gentle to his first wife and daughter Teofila. He was very anxious and suspicious man in questions related to his health. Baroque epoch also had left a mark on Radziwiłł’s personality and moulded his attitude to the death.